Research on Retinal and Iris Identification Systems - Sonmez, Yesim Ulgen (CNR Çevre [EN], 2017)
Biometrics is the science that analyzes biological data and also the technology that measures biological data. Biometric systems make identification or identity verification by using measurable, distinctive physical and behavioral properties of humans. The most widely used biometrics techniques rely on finger prints, palm, hand geometry, iris, retina, face, ear shape, vein, signature, hand writing and voice identification of an individual. Iris identification systems and retina identification systems are the most accurate and reliable identifying techniques. Iris is a circular structure surrounding the pupil, which determines eye color. The iris is a very rich tissue and it has a unique texture. This texture is different for each individual and it will stay same throughout their lives. Iris identification systems use the mathematical pattern-identification algorithms and statistical methods on individuals’ captured iris images. Retina, similar to iris, is unique for each person and has an unchanging texture throughout the life, except for some side effects of diseases. Retina that is located in the back side of the eye is responsible for vision. The mesh of blood vessels in retina is very complicated and distinctive. In retina identification systems, firstly, infrared light is radiated into the eye and blood vessels create unique reflections of this light. Retina identification is used in many areas from security systems to medical applications. This study examines and presents similarities and differences between two ocular biometric systems which are iris identification systems and retina identification systems. Analysis has also been carried out suing the findings of this study.
Keywords: Engineering; Mühendislik